THE APPLICATION OF MNEMONIC KEYWORD APPROACH AND ITS IMPACT ON FORMATIVE ASSESSMENT - A CASE STUDY - Shaira Ismail,; Azlin Shafinaz Mohamad Arshad,; Khiriah Ibrahim, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This case study investigates how individuals with a left-brain orientation comprehend and manage information overload using the Mnemonic Keyword Approach, focusing on students enrolled in the ENT300 course (Fundamentals of Entrepreneurship). The research aims to evaluate the impact of mnemonic techniques on academic performance in formative assessments. By analyzing student performance, the study seeks to determine the effectiveness of the Mnemonic Keyword Approach in enhancing understanding and information retention among left-brained individuals. The Mnemonic Keyword Method, which encodes information into easily retrievable and memorable formulas, was applied in teaching and learning activities. Using the Sommer-Sommer Brain Test, students were categorized by brain orientation to tailor the mnemonic techniques accordingly. Results indicated a significant improvement in knowledge retention, with assessment scores ranging from 75% to 97.75%. This improvement is attributed to the method's ability to provide meaningful coding and abbreviation formulas, enabling students to construct answers based on keywords. The study concludes that the Mnemonic Keyword Approach is a highly effective strategy for memorizing and retaining knowledge, as it facilitates the encoding and retrieval of information in a structured manner, thereby enhancing students' understanding and performance in formative assessments.